Educational agents and institutions called into action in suicide prevention, intervention, and postvention - De Oliveira, Janaina Minelli; Dueñas, Jorge-Manuel; Morales-Vives, Fabia; Gallardo-Nieto, Elena (Frontiers in Psychology, 2023)
Suicide is the second leading cause of death in the 15 to 29 age group worldwide, and is a severe public health problem. Adolescent and young adult individuals attend educational institutions which can play an essential role in detecting and preventing suicide. For this reason, the purpose of this research is to identify what educational institutions and agents are called into action in suicide prevention, intervention, and postvention. The method of systematic review of the literature based on the PRISMA protocol was used. The review protocol was registered in PROSPERO (PROSPERO 2020 CRD42020189127). The systematic review yielded 66 articles published between 1990 and February 2023. The results show that a wide variety of educational stakeholders are required to intervene for suicide prevention, interventions and postvention between primary education and college. The study describes the different programs that have been provided, the countries in which they have been implemented and the agents who have been targeted. It also identifies gaps in the research on suicide in the educational field. Overall, educational suicide initiatives report positive effects on participants’ understanding, attitudes, and beliefs regarding suicide and suicide prevention, although some studies have expressed some caution.